Redefining flux ropes in heliophysics - Nieves-Chinchilla, Teresa; Pal, Sanchita; Salman, Tarik M.; Carcaboso, Fernando; Guidoni, Silvina E.; Cremades, Hebe; Narock, Ayris; Balmaceda, Laura A.; Lynch, Benjamin J.; Al-Haddad, Nada; Rodríguez-García, Laura; Narock, Thomas W.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
This paper underlines the lack of fundamental understanding of heliospheric flux ropes and provides the motivation to significantly improve the status quo of flux rope research through novel and requisite approaches. The recommendations put forward in this paper will broaden the in-depth knowledge of our nearest star, its dynamics, and its role in its sphere of influence, the heliosphere.